Grayscale Ultrasonography in the Assessment of Regional Lymph Nodes in Oral Cancer and its Correlation with TNM Staging and FNAC - Ankur Aggarwal; M Jonathan Daniel; S V Srinivasan; Charles P Sargouname (Wolters Kluwer Medknow Publications, 2011)
Objectives: The purpose of the study was to evaluate the role of grayscale ultrasound (US) in differentiation of benign from malignant lymph nodes in oral cancer patients and to correlate the ultrasonographic features with TNM staging and FNAC findings of cervicofacial lymph nodes. Methods: In the study, 34 patients with histopathologically proved oral cancer presenting with enlarged superficial cervicofacial lymphadenopathy were included. The clinical, ultrasonographic and fine needle aspiration cytology (FNAC) findings were compared in these patients. Patients were assessed for presence of nodes, their size, ratio of maximum longitudinal diameter to maximum transverse diameter (L/T) and echogenicity. All patients then underwent fine needle aspiration cytology of the lymph nodes and the slides were examined for the presence of malignant cells. Results: It was found that ultrasonography had assessed the status of 28 nodes positively out of 34 nodes for metastasis when compared with results of FNAC. Thus, ultrasonography had a sensitivity of 75% and specificity of 86% in detecting the metastatic nodes when compared with FNAC taken as standard in the detection of metastatic nodes. Conclusion: The lymph node status can be assessed successfully by ultrasonography preoperatively for the presence of metastasis in majority of cases. Therefore, ultrasonography was found to be efficient and cost-effective preoperatively, in planning appropriate management in oral cancer patients.